Dinamika Kota Batam sebagai Kota Wisata Tahun 2007 – 2024 - Fadhiel Muhammad Akbar; Anak Agung Inten Asmariati; Anak Agung Ayu Rai Wahyuni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Tourism plays a strategic role in national economic development, including in Batam City. Batam's geographical location, directly bordering Singapore and Malaysia, makes it a main gateway for international tourists visiting Indonesia. Since being designated as a Free Trade and Free Port Area through Government Regulation No. 46 of 2007, Batam has transformed from an industrial zone into a tourist city. This study analyzes the dynamics of Batam's development as a tourist city during the 2007–2024 period using a descriptive analytical historical approach, drawing on primary and secondary sources. The findings indicate that Batam's tourism development has been influenced by its strategic position, policy support, and improvements in infrastructure and connectivity. The institutional integration between the Batam City Government and the Batam Authority (BP Batam) through the ex-officio leadership policy since 2019 has strengthened the synergy between regional economic management and tourism development. The establishment of the Nongsa Digital Park SEZ (2021) and the Batam International Tourism and Health SEZ (2024) mark important milestones in the transformation toward a modern tourism destination based on digital, health, and MICE sectors. This reflects Batam's efforts to enhance its global competitiveness and realize sustainable tourism development in Indonesia's border region.